A critical comparison of natural enzymes and nanozymes in biosensing and bioassays - Ashrafi, Amir M; Bytesnikova, Zuzana; Barek, Jiri; Richtera, Lukas; Adam, Vojtech (Biosensors & bioelectronics, 2021)
Nanozymes (NZs) are nanomaterials that mimic enzyme-like catalytic activity. They have attracted substantial attention due to their inherent physicochemical properties for use as promising alternatives to natural enzymes (NEs) in a variety of research fields. Particularly, in biosensing and bioassays, NZs have opened a new horizon to eliminate the intrinsic limitations of NEs, including their denaturation at extreme pH values and temperatures, poor reusability and recyclability, and high production costs. Moreover, the catalytic activity of NZs can be modulated in the preparation step by following an appropriate synthesis strategy. This review aims to gain insight into the potential substitution of NEs by NZs in biosensing and bioassays while considering both the pros and cons.
Keywords: biotest; Natural enzymes; biosenzitivní techniky; nanostruktury; Bioassay; Catalysis; Enzymes; Nanostructures; Nanozymes; enzymy; katalýza; Biosensing; Biological Assay; Biosensing Techniques